2018
DOI: 10.1097/dss.0000000000001381
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Window Technique Using CO2 Laser, and a Review of Methods for Nail Matrix Biopsy of Longitudinal Melanonychia

Abstract: The window technique assisted by CO2 laser and dermoscopy can be a minimally invasive and effective method for nail matrix LM biopsy under local anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Therefore, the authors used a specialized window technique with punch biopsy that targets only the nail matrix where the main pathologic change occurs. This is a variant technique that we used for longitudinal melanonychia 10 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the authors used a specialized window technique with punch biopsy that targets only the nail matrix where the main pathologic change occurs. This is a variant technique that we used for longitudinal melanonychia 10 …”
Section: Discussionmentioning
confidence: 99%
“…This procedure can be performed by first using a 4–6 mm punch to remove the nail plate, following which physicians can perform a smaller punch (2–4 mm) to acquire the nail matrix tissue 14 . Although the technique is simple, there is a risk of obtaining false‐negative results, as the pigmented patterns in the matrix cannot be thoroughly identified during the procedure 48 …”
Section: Diagnosismentioning
confidence: 99%
“…14 Although the technique is simple, there is a risk of obtaining false-negative results, as the pigmented patterns in the matrix cannot be thoroughly identified during the procedure. 48 When pigmented bands are located in the lateral third of the nail plate, a lateral longitudinal nail biopsy can be performed. The excision extends from the most proximal aspect of the nail matrix to the digit pulp.…”
Section: Biopsy Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] The nail window technique assisted by a CO 2 laser is an auxiliary method before nail surgery that creates a window on the nail plate and makes exposure of the pigmented nail matrix easier. 10 A previous study has shown that the rate of recurrence of nail pigmentation was as high as 70% after tangential excision of pigmented nail matrix lesions responsible for LM. 8 This may due to an incomplete excision of the responsible lesions or repopulation of the melanocytes from the ventral surface of the pigmented nail plate.…”
mentioning
confidence: 96%